Removal of Methyl Violet Dye Using (Zno/Mwcnts) Nanomaterial - Amir Fahdil Dawood AL-Niaimi; Esraa Ibraheim Mahmood (Academic Science Journal)
The composite (0.8/0.018ZnO/MWCNTs) (w/w) of the nanocomposite was used to remove the methyl violet dye from its aqueous solution. Batch system was used in the adsorption process, and the compounds were diagnosed using (FTIR, XRD, BET, EDX, FE-SEM) techniqiues. It was found that zinc oxide has a surface area of 27.71 m2.g-1, and the average particle size is 45 nanometers. Z nO/MWCNTs surface area is 38.85 m2.g-1, and the effectiveness of using the compound to remove methyl violet dye from aqueous solution was evaluated using batch adsorption. The amount of dye removal by the adsorbents increases with the increase in contact time. The ideal adsorption was achieved in 40 minutes. The pH of the aqueous solution has an effect on the adsorption process. The largest removal of dye was achieved at pH=7, and the adsorption isotherms were studied using Langmuir isotherm and Freundlich model, where it was found that they are more consistent with the Freundlich isotherm. The kinetics of the reaction were studied using the pseudo-first-order model, and the adsorption process was more consistent with the pseudo-second-order kinetics.